Pengaruh Pendekatan Etnomatematika Berbasis Geometri Arsitektur Istana Maimun terhadap Pemahaman Aturan Sinus dan Kosinus pada Siswa - Lubis, Farhan; Nuh, Muhammad (Jurnal Pendidikan Matematika : Judika Education, 2024)
This study aims to test the influence of the ethnomathematical approach based on the geometry of the Maimun Palace architecture on the understanding of the sine and cosine rules of class X students in MAN 2 Model Medan. The method used is a quasi-experimental design with a pretest-posttest control group; that is, the experimental group is taught using an ethnomathematical approach, while the control group uses conventional learning. The results showed that the independent sample t-test produced a significance value (p < 0.01), which means that there was an influence of the ethnomathematical approach based on the geometry of the Maimun Palace architecture on the understanding of the rules of sine and cosine in students. The n-gain value test of the experimental group obtained 0.85, included in the high category, while the control group 0.65 belonged to the medium category. The conclusion of the study was obtained that ethnomathematical approaches based on local culture, such as the architecture of the Maimun Palace, are not only effective in improving students' understanding of mathematical concepts but also enriching the learning experience based on local cultural wisdom. Keywords : Ethnomathematics, Maimun Palace, Concept Understanding.